The role of peripheral cues in judgments of difficulty - Vangsness, Lisa (Kansas State University, 2019)
Judgments of difficulty (JODs) can be used to inform effort allocation strategies and subsequent performance. This dissertation integrates several models to advance specific hypotheses regarding the role that feedback, a performance-based peripheral cue, plays in these processes. These predictions are tested in two experiments that manipulate when and how feedback information is made available. In Experiment 1, people alternated between observing and performing a visual search task; performance-based peripheral cues informed JODs to a lesser degree until people had a chance to perform the task themselves, suggesting that receiving feedback on one’s performance informs self-efficacy beliefs. In Experiment 2, people learned about the incentive structure of the environment at different times. Incentives changes peoples’ effort allocation strategies, but the way in which it did so depended on when this information was made available. People who learned of the incentives in advance used this information to engage in preventative effort allocation strategies, while those who learned of the incentives through feedback alone engaged in compensatory effort allocation strategies. Together, these results disambiguate when and how people use performance-based peripheral cues to make JODs, and provide information about how the environment can be structured to facilitate learning and behavioral change.
Keywords: Task difficulty; Cues to difficulty; Judgments of difficulty; Performance-based feedback; Effort allocation strategy; Risk mitigation